RENEGOTIATION MINING CONTRACT: LEGAL PARADIGM RECONSTRUCTION EFFORTS - -, Marilang (Journal of Humanity, 2014)
Renegotiation contract mining is not a priori notion that was born but is driven by the fact that empirical Work Contract (KK) and coal mining concessions of the Works Agreement (Cca) that are valid for this resulted in profits which are not comparable between countries with investors (domestic and foreign). In addition, Law No. 4 of 2009 about Mineral and Coal Mining (minerba) through article 169 have been injected that though the mining contracts during the validity of this, still respected until the end, however, if the implementation of these contracts give rise to distortions for the national interest, then the Government must encourage the investors to do Renegotiation against existing contracts to comply with legislation minerba forever within a period of one year since the enactment of the legislation this minerba. Renegotiation mining contracts that have been approved on the fact of the matter is simply an attempt to reconstruct the ruling paradigm, so with that paradigm shift, both parties can reach the intersection for the benefit of both parties, i.e. the parties proportionately Indonesia suffered no losses on the one hand, and the benefit of the domestic and foreign investors remain in reasonable limits on the other.Â